UNGKAPAN EMOSI PADA ANAK USIA 1 TAHUN 6 BULAN DALAM KAJIAN PSIKOLINGUISTIK - Ahdimas Husnun Khotami (Universitas Sarjanawiyata Tamansiswa, 2020)
The psycholinguistic study presented by Piaget examines the stages of language development, aged 1-2 years, including the holophrastic stage (one-word speech). The speech that comes out of the child is very comforting by moderate circumstances, such as sad, happy or uncomfortable. This research is a case study that emphasizes emotions in children aged 1-2 years. The conditions that occur in children will provoke speeches that express their condition. Based on data analysis obtained from voice recordings, it appears that children aged 1-2 years only master the linguistic aspects of phonology and cannot pronounce vocabulary clearly. The method used is descriptive qualitative which analyzes the meaning, cause and effect of the vocabulary that comes out of the child.Â